High School EFL Teachers’ Continuous Professional Development: Target Needs, Reflection and Challenges - Mekie, Mulualem Eshete (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2023)
This research investigated the high school EFL teachers’ continuous professional development target needs, reflection and challenges. Further, the target needs of the EFL teachers were analyzed by adapting Hutchinson and Waters’ model (1987). The data were collected using a test, questionnaire (consisted of five parts), and interview; these were administered to 20 high school EFL teachers. A test was administered to identify EFL teachers' present situation and difficulties, and questionnaire parts 1, 2 and 4 dealt with the EFL teachers' difficulties, needs and purposes in the program. Moreover, these were used to identify EFL teachers’ target needs centered on their lacks, necessities, and wants to function in the target situation effectively. Parts 3 and 5 concerned high school EFL teachers' reflection and challenges in the professional development program they are involved in.Additionally, interviews were conducted with the high school EFL teachers to gather data to examine in-depth results of the target needs, reflections and challenges. The results suggested that the high school EFL teachers have different views of their lacks, wants and necessities. The findings also demonstrated that the high school EFL teachers reflected that the current professional development program practicing in their school was never conducted to help EFL teachers develop their profession. Finally, the result revealed that high school EFL teachers face various challenges in the current program they are taking. Therefore, the professional development should be revised according to EFL teachers’ target needs, reflections and challenges.